2015
DOI: 10.5430/irhe.v1n1p107
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Members' Experiences of Cyberbullying by Students at One Canadian University: Impact and Recommendations

Abstract: This two-phase mixed methods study adopted online survey and individual interview questions to explore faculty members' experiences of cyberbullying by students at one Canadian university. Foucault's (1994) power relations theory was used to explore the power dynamic that can exist in the student-faculty relationship. The study found that cyberbullied faculty members were commonly female, over 40 years of age, English-speaking Canadian citizens, and held fulltime rank. Cyberbullying occurred namely via email, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 84 publications
3
43
0
1
Order By: Relevance
“…Student-on-faculty harassment is a form "academic contrapower harassment" (ACPH), which "occurs when someone with seemingly less power in an educational setting [e.g., a student] harasses someone more powerful [e.g., a professor]" (Lampman, Crew, Lowery, & Tompkins, 2016, p. 169). Studies demonstrate that faculty members across genders are harassed by students, through a variety of means, and for a variety of reasons (Blizard, 2016;Lampman, 2012;Lampman et al, 2016;MacLennan, 2002). For example, Blizard's (2016) study of one Canadian university found that student-on-faculty cyberbullying mainly, but not exclusively, stems from students' dissatisfaction with their grades.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Student-on-faculty harassment is a form "academic contrapower harassment" (ACPH), which "occurs when someone with seemingly less power in an educational setting [e.g., a student] harasses someone more powerful [e.g., a professor]" (Lampman, Crew, Lowery, & Tompkins, 2016, p. 169). Studies demonstrate that faculty members across genders are harassed by students, through a variety of means, and for a variety of reasons (Blizard, 2016;Lampman, 2012;Lampman et al, 2016;MacLennan, 2002). For example, Blizard's (2016) study of one Canadian university found that student-on-faculty cyberbullying mainly, but not exclusively, stems from students' dissatisfaction with their grades.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 99%
“…Studies demonstrate that faculty members across genders are harassed by students, through a variety of means, and for a variety of reasons (Blizard, 2016;Lampman, 2012;Lampman et al, 2016;MacLennan, 2002). For example, Blizard's (2016) study of one Canadian university found that student-on-faculty cyberbullying mainly, but not exclusively, stems from students' dissatisfaction with their grades. Although some research explores contrapower harassment and bullying, including its negative impacts on faculty members, public attention and university resources largely address noncontrapower forms of harassment, such as faculty-on-student harassment and faculty-on faculty harassment.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Live-streaming these conversations could result in embarrassment, loss of dignity, as well as emotional and social isolation that could affect faculty mental health and overall psychological well-being (Kolowich & Quintana, 2017). Although research findings (Blizard, 2016;Eskey & Roehrich, 2015) indicated that the number of college faculty reporting cyberbullying is small, it could be argued that cyberbullying of college faculty is not a myth. Forbes Magazine used data from an ARS to rank U.S. colleges and universities (Bleske-Rechek & Michels, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%